Motor Cortex Excitation/Inhibition Imbalance in Young Adults With Autism Spectrum Disorder: A MRS-TMS Approach - Bernardino, Inês; Dionísio, Ana; Violante, Inês R.; Monteiro, Raquel; Castelo-Branco, Miguel (Frontiers in Psychiatry, 2022)
Excitatory/inhibitory imbalance has been suggested as a neurobiological substrate of the cognitive symptomatology in Autism Spectrum Disorder (ASD). Studies using magnetic resonance spectroscopy (MRS) attempted to characterize GABAergic and Glutamatergic neurotransmission in ASD. However mixed findings have been reported. Here, we investigated this hypothesis by implementing a multimodal approach combining MRS and transcranial magnetic stimulation (TMS) to characterize both neurochemical and physiological aspects of GABAergic neurotransmission in ASD. A group of 16 young ASD adults and a group of 17 neurotypicals participated in this study. We employed one MRS session to assess motor cortex GABA+ and Glx levels using MEGAPRESS and PRESS sequences, respectively. Additionally, a TMS experiment was implemented including paired-pulse (SICI, ICF and LICI), input-output curve and cortical silent period to probe cortical excitability. Our results showed a significantly increased Glx and decreased GABA+/Glx, with unchanged GABA+ levels in the ASD group compared with controls. Single TMS measures did not differ between groups, although within-group analysis showed impaired inhibition in SICI5ms, in ASD. Importantly, we observed a correlation between GABA levels and measures of the input-output TMS recruitment curve (slope and MEP amplitude) in the control group but not in ASD, as further demonstrated by direct between group comparisons. In this exploratory study, we found evidence that altered glutamatergic neurotransmission and intracortical inhibitory pathways may contribute to ASD excitatory/inhibitory imbalance while highlighting the relevance of studying GABAergic neurotransmission from complementary perspectives, using both MRS and TMS techniques in larger-scale studies..